My Name Is Lola - Rozsa, Lola; Sparks, Susie (The West, 2013)
This book contains the collected memories of Lola Rozsa - of her life and service to her family, her church, and her community as she and her husband, Ted, made their way from the tiny towns of the Depression-era, dust bowl southern plains to the burgeoning oil fields of Alberta in 1949. As Ted struggled to build his first seismic company, Lola raised their children in Calgary, an environment far different from the home in Texas she desperately missed. However, the values taught her by her preacher father stood her in good stead as she immersed herself in service for her new community. For the next sixty years, as Ted prospered, they made Calgary their home and, along with other industry pioneers, helped to build many of the enduring cultural institutions in Calgary.